HUBUNGAN KUALITAS PELAYANAN DENGAN KEPUASAN PASIEN RAWAT INAP BPJS KELAS III (STUDI KASUS DI RSU HAJI SURABAYA) - Fitria, Aidil (JPAP: Jurnal Penelitian Administrasi Publik, 2017)
Service Quality Relationship With The Satisfaction Of Interpatient Patient Patients Class By III. Health service is a basic right owned by every individual and must be fulfilled by the government, along with improving the living standards of the better and see the performance of government bureaucracy that is still far from public expectations, the government in this case the General Hospital is required to improve itself improve health services for the community, especially services at inpatient BPJS class III. Since since BPJS and other government programs, currently based on assessment, the quality of health services, especially inpatient care, is more likely to decrease if the value of patient satisfaction.             This study aims to analyze the quality of service with patient satisfaction through seven dimensions of health quality consisting of Guarantees, Empathy, Reliability, Responsiveness, Physical Views, Medical Services and Professionalism. Dimension is used to analyze the quality of service with satisfaction of inpatient BPJS class III in RSU Haji Surabaya.             The method used in this study using descriptive qualitative methods, data sources used are primary data and secondary data. In the study the authors also used research techniques in the form of observation / observation, interviews and documentation in order to obtain primary data to find out how the quality of service with patient satisfaction BPJS class III in RSU Haji Surabaya.             Based on the result of the analysis and the discussion that has been done, the quality of service with the satisfaction of the inpatients of BPJS class III hospital in RSU Haji Surabaya, according to the dimension of guarantee, empathy, reliability, responsiveness, medical service and professionalism of inpatient grade III service at RSU Haji Surabaya said good, so that patients feel satisfied, while the physical display dimensions are still said to be quite good and patients feel quite satisfied. This is evidenced by the room is quite hot and the bathroom can be said not too clean. Keywords: Quality of service, Patient satisfaction, The quality of service with the patient relationship satisfaction